Evaluation of a Tangential Map-Based Nomogram for Intrastromal Corneal Ring Segments’ Implantation in Keratoconus: One Year Results - Adel Galal Zaky; Mahmoud Tawfik KhalafAllah; Abdelrahman Elsebaey Sarhan; Moataz Faiz Elsawy (Journal of Ophthalmology)
Purpose. To evaluate a new tangential map-based nomogram versus the axial map-based nomogram for ICRS in keratoconus. Methods. A prospective case series study including 64 eyes of 64 patients who underwent ICRS implantation. Cone location was determined for each eye with two maps: the axial and the tangential. Appropriate ring selection was determined using two surgical nomograms: axial map-based and tangential map-based. Visual, refractive, and topographic outcomes were assessed before, as well as at 3, 6, and 12 months after ICRS implantation. Results. The cone location, and consequently the ring selection, was significantly different in the two nomograms with a “centralization tendency” in the tangential map. In the axial group, UDVA and CDVA improved from 0.12 ± 0.04 and 0.24 ± 0.08 to 0.28 ± 0.08 and 0.4 ± 0.1, respectively. Similarly, MRSE substantially decreased from −6.7 ± 3.3 to −1.2 ± 1.1D at 12 months after the procedure. In the tangential group, UDVA and CDVA improved from 0.09 ± 0.06 and 0.2 ± 0.1 to 0.5 ± 0.2 and 0.7 ± 0.2, respectively. MRSE substantially decreased from −4.9 ± 1D to −1.00 ± 1.6D at 12 months after the procedure. The UDVA gain was significantly higher in the tangential group: 0.35 compared to 0.15 at 12 months, P=0.01∗. Similarly, the gain in the CDVA was 0.4 and 0.15 in the tangential and axial groups, respectively, at 12 months, P=0.003∗. At 12 months, the tangential map showed superiority in UDVA, CDVA, and MRSE in the peripheral cone location, but not the central and paracentral ones. Conclusion. The tangential map-based nomogram attained better visual and refractive outcomes at 1 year. In addition, the cone location was significantly different between both maps with a centralization tendency in the tangential one.